THE LEGAL STATUS OF CHILDREN NOT IN MARRIAGE FROM THE PERSPECTIVE OF POSITIVE AND ISLAMIC LAW - Sunanta Sunanta (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The study aims to present the phenomena, their contributing variables,and the effects of children's legal status outside of marriage. In thisinstance, the author presents the Cirebon Religious Court's DeterminationNo. 13/Pdt.P/2022/PA—CN case study. Three methods are used to acquiredata: documentation, interviews, and observation. Editing, classification,verification, and analysis are among the methodical steps used in dataprocessing and analysis. Based on the findings of this study, it can be said that children lose some of their rights to their biological parents when a marriage fails or is harmed because it does not meet Islamic law's conditions for marriage harmony. The fact that Petitioner I married Petitioner II within the iddah period from her ex-husband is one of the most deadly reasons for marital dissolution in this instance. The child is the most disadvantaged party. Except for a required will, a child cannot be assigned to his biological father, loses guardianship status, and is not entitled to an inheritance in the event of his father's death. The Constitutional Court stepped in to provide clarification in response to this debate by ruling that biological fathers must continue to pay for their children's upbringing, education, and medical care until adulthood.